Video Development Of School Profiles As Promotional Media To Promote Increased Accreditation - Febriadin Anggriawan; Zila Razilu; Hendra Nelva Saputra (Jurnal Amal Pendidikan, 2023)
The development of school video profiles is not just a trend, but an urgent need in an increasingly competitive and technology-based world of education. The purpose of this research is to create a video profile of one of the PAUD Muhammadiyah schools in Kendari City. The Villamil-Molina method is divided into five phases: development, preproduction, production, post production, and delivery. The video profile developed by the school has been qualified to be a school promotion medium with results as a 2 minute 45 second video in MP4 format and has been saved on google drive. Based on the information expert test, an average score of 88.33% can be interpreted as indicating that the information presented in this profile video is already in line with the conditions of the school. The information shown in this video is the school vision, school mission, school facilities, and the number of teachers and educators. The media expert test results obtained an average percentage score of 85.75% that can be interpreted that the video of the school profile developed is well qualified and meets media evaluation indicators that focus on text and image synthesis, video quality, video presentation, and video editing techniques.